The relevance of alpha phase in human perception. (November 2019) - Ruzzoli, Manuela; Torralba, Mireia; Morís Fernández, Luis; Soto-Faraco, Salvador
Abstract: Neural oscillations in the low frequencies, roughly in the alpha band (α, 5–15 Hz), have been suggested to act as a gateway from sensation to perception. This hypothesis assumes discrete perception. In particular, the amplitude and the phase of the low frequency rhythm entails a cortical mechanism which paces the access of sensory information into the cognitive system. Evidence supporting this idea includes correlations between the phase of neural oscillations and behavioral performance in perception, spatial attention and working memory. Despite a widespread confidence in the theory, these findings have been mostly based on a varied range of exploratory approaches and inferential group statistics. Here, we aimed at validating the involvement of low frequency cortical rhythm in perception and at providing a clear-cut EEG analysis pipeline. Such an analytical pipeline should support the adoption of a hypothesis-driven framework for future replications and applications. The design, the analyses and the statistical power of the present experiment were based on prior studies in which phase opposition was successfully found. However, our results provide evidence for the involvement of pre-stimulus oscillatory alpha amplitude but not phase in perception. We discuss the null findings from the present study within the existing literature.